2013
DOI: 10.1155/2013/186759
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Two Angiotensin Receptor Blockers on Vascular Hemodynamics, Arterial Stiffness, and Oxidative Stress in Patients with Mild to Moderate Hypertension: An Open Label Parallel Group Study

Abstract: Introduction. We studied the acute effects of Olmesartan and Telmisartan at baseline and at the end of four weeks on indices of hemodynamics (heart rate HR, blood pressure BP), vascular (carotid femoral pulse wave velocity cf PWV, digital arterial tone expressed as Reflection index RI, and endothelial dependent vasodilator response EDVR), and oxidative stress (serum Malondialdehyde MDA) in hypertensive patients. Materials and Methods. The eligible patients were randomly allocated to either 20 mg Olmesartan or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
6
2
Order By: Relevance
“…It is well known that endothelial dysfunction, occurs in diabetic complications (6), associates with atherosclerotic progression (4) and elevates in oxidative stress. In diabetic SHRs, variable observation in terms of increased or decreased SBP and MAP are reported (41), (42), whereas, in our study ndings, the MAP and SBP values of diabetic SHRs were considerably higher, which could be due to the rapid destruction of nitric oxide (NO) in STZ induced SHRs (43), although, diminished NO bioactivity and bioavailability are key characteristics for arterial hypertension and endothelial disorders (44).…”
Section: Discussioncontrasting
confidence: 57%
“…It is well known that endothelial dysfunction, occurs in diabetic complications (6), associates with atherosclerotic progression (4) and elevates in oxidative stress. In diabetic SHRs, variable observation in terms of increased or decreased SBP and MAP are reported (41), (42), whereas, in our study ndings, the MAP and SBP values of diabetic SHRs were considerably higher, which could be due to the rapid destruction of nitric oxide (NO) in STZ induced SHRs (43), although, diminished NO bioactivity and bioavailability are key characteristics for arterial hypertension and endothelial disorders (44).…”
Section: Discussioncontrasting
confidence: 57%
“…However, many studies do not support our findings. Pathapati et al; [20] found no statistically significant difference between the two groups with respect to reduction in SBP and DBP both. In another study by Luis DA et al; [21] both drugs had similar blood pressure lowering effect in hypertensive obese patients.…”
Section: Baseline Investigations Done In All Patients -mentioning
confidence: 89%
“…Under water shortage conditions, excessive loss of perspiration may damage the body's cardiovascular and thermoregulatory function (7)(8)(9). In response to the high temperature, the human body needs heat dissipation and expansion of body surface blood vessels, the amount of blood in the body surface increases, and the amount of blood supply for heart, cerebrovascular is relatively reduced, leading to cerebral ischemic and hypoxic reactions (10,11). The experiment results showed that, with the increase of heat exposure intensity, the rat heart rate had a tendency to slow down.…”
Section: Discussionmentioning
confidence: 99%